Phase I lead‐in and subsequent randomized trial assessing safety and modulation of regulatory T cell numbers following a maximally tolerated dose doxorubicin and metronomic dose cyclophosphamide combination chemotherapy protocol in tumour‐bearing dogs1. (1st November 2015) - Rasmussen, R. M.; Kurzman, I. D.; Biller, B. J.; Guth, A.; Vail, D. M.
Abstract: Maximally tolerated dose (MTD) and metronomic dose chemotherapeutic approaches alter the immune system and the angiogenic process in different yet potentially complementary ways. A combination of MTD doxorubicin (MTD‐DOX) and metronomic cyclophosphamide (mCTX) protocol was evaluated for safety and effect on circulating regulatory T (Treg) cells. We found that mCTX can be safely administered with MTD‐DOX in tumour‐bearing dogs. Both combination DOX/mCTX and single‐agent DOX resulted in significant depletions of circulating lymphocytes throughout the chemotherapy cycle without apparent selectivity for Tregs. The indiscriminant lymphocyte depletions were similar between dogs randomized to receive DOX and dogs randomized to receive DOX/mCTX, suggesting this effect is because of DOX alone. These findings may have implications as to the therapeutic benefit (or lack thereof) of concurrent combination MTD and metronomic protocols. Future investigations are required to determine the effects and indeed the efficacy of concurrent versus sequential applications of MTD and metronomic chemotherapy protocols.